1990
DOI: 10.1557/proc-193-235
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Microscopic Properties of Semiconducting Grain Boundaries and their Orientation

Abstract: The microscopic structure of a tilt and a twist boundary in germanium are explored using a state-of-the-art total energy calculation. The structure of the tilt boundary (Σ = 5 (310)) is found to be simple as it exhibits a well defined minimum energy structure, consistent with previous experimental and theoretical results on this and other tilt boundaries. The structure of the twist boundary (Σ = 5 (100)), however, is found to be very complex. The boundary bonds are distorted and weak, and their weakness makes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…A similar configuration was observed in Ge [100]. All these results can be understood from the morphology of the structural units [101,102,35]. For tilt boundaries, it is rather easy to construct stable structural units consisting of four-fold coordinated atomic rings, because the directions of dangling bonds on both grains are often parallel to a common plane and the period along the rotation axis is very short.…”
Section: Twist Boundaries In Si or Gesupporting
confidence: 62%
See 1 more Smart Citation
“…A similar configuration was observed in Ge [100]. All these results can be understood from the morphology of the structural units [101,102,35]. For tilt boundaries, it is rather easy to construct stable structural units consisting of four-fold coordinated atomic rings, because the directions of dangling bonds on both grains are often parallel to a common plane and the period along the rotation axis is very short.…”
Section: Twist Boundaries In Si or Gesupporting
confidence: 62%
“…All these features are quite different from coincidence tilt boundaries. The boundary-energy values are several times larger than those of tilt boundaries [101].…”
Section: Twist Boundaries In Si or Gementioning
confidence: 73%
“…Recently we have made a thorough investigation of the ⌺5 boundary and found that there are ordered, low-energy structures for this boundary, which were confirmed by firstprinciples simulations. 8 Our findings contradicted earlier simulations of twist boundaries, 5,6,[9][10][11][12][13] which did not find our low-energy ordered structures and which we attributed to inadequate sampling of configurational phase space.…”
Section: Introductioncontrasting
confidence: 99%
“…Our results indicate that earlier simulations 5,6,[9][10][11][12][13] of this and most likely other twist boundaries in covalent semiconductors have failed to locate the global energy minima. There are two principal reasons.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation